KESIAPAN MENGHADAPI BENCANA BANJIR BERBASIS GENDER DI KELURAHAN TANJUNG KECAMATAN RASANAE BARAT KOTA BIMA: READINESS TO FACING GENDER-BASED FLOOD DISASTERS IN TANJUNG VILLAGE, RASANAE BARAT DISTRICT, BIMA CITY - Ardian Adhiwijaya; Andi Adriana Amal (Akademi Keperawatan Yarsi Samarinda, 2024)
Readiness to face flood disasters remains a problem that needs to be addressed. This research aims to determine flood disaster preparedness based on gender. The study employs a descriptive observational design with a cross-sectional approach. The research sample consists of 60 heads of households selected through simple random sampling techniques. Data collection utilizes a disaster preparedness instrument, followed by statistical analysis using the Mann-Whitney test. The results of this research indicate no statistical difference in preparedness between men and women in facing floods. However, item analysis reveals that men tend to take the initiative to act, while women are more dominant in planning for flood preparedness. Considering gender perspectives is essential in facing floods to empower individuals according to their potential.